The Effects of Light Guide Thickness on the Accuracy of Position Estimation, Linearity, and Uniformity Responses of Anger Camera: a Monte Carlo Study - Hamidreza Hemmati; Alireza Kamali-Asl; Reza Haghshenas (Frontiers in Biomedical Technologies, 2015)
Purpose- Some practical and theoretical efforts have been made to investigate the effects of designing parameters on the performance of anger camera. In this study, the effects of light guide thickness on the accuracy of position estimation, linearity, and uniformity response of a typical gamma camera has assessed using Geant4 Monte Carlo (MC) simulation toolkit.